Pelaksanaan Perjanjian Pengelolaan Pertanian Pada Masyarakat Adat Kampar - GM Manik, Rahmat; Firmanda, Hengki; Darnia, Meriza Elpha; Salami, Mumaddun Khaerudin (Faculty of Law, Universitas Riau, 2024)
Agricultural land has a social function whose benefits are very helpful to improve the welfare of the community in order to realize social justice. Land exploitation agreements with production sharing are regulated in customary law based on an agreement between the landowner and the tenant farmer in return for the results agreed by both parties. In its development, the production sharing agreement is regulated through Law Number 2 of 1960 Concerning Production Sharing Agreements. In the Kampar Regency area, which has indigenous peoples and still upholds life based on customs or still maintains local wisdom. Access to agricultural management is an important aspect for indigenous peoples, especially for indigenous groups that are still dependent on natural resources. In managing agricultural land, indigenous peoples in Kampar Regency, one of which is carried out by cooperating in agricultural land management between fellow indigenous peoples. The urgency of this writing is to see the implementation of agricultural management agreements in indigenous peoples in Kampar Regency. The results of this study are that not all indigenous peoples carry out agricultural land management agreements, agricultural management agreements are carried out because the majority of the population works as farmers, but not all people have land for farming. Agreements are made in writing for agricultural management. Obstacles to the Implementation of profit-sharing agreements in the indigenous people of Kampar Regency include When implementing the Harvest, the cultivator does not share the results in accordance with the agreement. Discrepancies in understanding between indigenous peoples as cultivators and indigenous peoples as landowners. The lack of understanding of indigenous peoples regarding agricultural profit-sharing arrangements and tenurial conflicts that still occur in Kampar have also become obstacles in the implementation of agricultural land management agreements in Kampar indigenous peoples